What Drivers Internal Control System in Islamic Microfinance Institution? - Putri Catur Ayu Lestari; Putri Kamilatur Rohmi (Darul Yasin Al Sys, 2026)
Baitul Maal wat Tamwil (BMTs) in Indonesia continue to face internal and external challenges that underscore the need for effective internal control systems. Although previous research has examined the effectiveness and contribution of internal control systems, evidence regarding the internal and external factors driving their implementation in BMTs remains limited. Drawing on institutional theory, this study analyzes the effects of management commitment, environmental uncertainty, and external pressure on internal control system implementation. A quantitative explanatory survey was conducted involving 95 managers of BMTs affiliated with PUSKOPSYAH D.I. Yogyakarta. Data were collected using a four-point Likert-scale questionnaire administered through the control self-assessment method and analyzed using partial least squares structural equation modeling (PLS-SEM). The findings demonstrate that management commitment, environmental uncertainty, and external pressure have positive and significant effects on internal control system implementation. Management commitment exerts the strongest effect (β = 0.425), followed by environmental uncertainty (β = 0.296) and external pressure (β = 0.224), while the model explains 41.2% of the variance in internal control system implementation. These findings highlight the central role of managerial commitment and demonstrate that BMTs adapt their internal controls in response to environmental uncertainty and external pressures. This study extends the application of institutional theory to Islamic microfinance by providing empirical evidence on the internal and external determinants of internal control system implementation in BMTs. Further research should broaden the geographical scope, employ longitudinal designs, and examine additional determinants, including human resource competence, organizational culture, information technology, and supervisory effectiveness.